Designing android-based learning media using the rapid application development method - Reni Rahmadani; Khofifah Qalbun Salima; Adilla Ulfhi; Tansa Trisna Astono Putri; Muhammad Dominique Mendoza (SEAN Institute, 2024)
Android-based learning multimedia is a learning media used in the learning process because it can be used anytime and anywhere. Several barriers to learning have been identified in basic computer and network courses. Based on observations made on the introduction of computer hardware and software, the barriers found are the relatively low level of student knowledge of the subject matter, student involvement in the learning process is also low and the learning media still uses power point containing learning theories derived from books. This research uses UML as a multimedia development tool along with RAD (Rapid Application Development) methodology. Based on the results of trials conducted on students, the results obtained that students feel very interested in learning using android-based interactive multimedia in basic computer network subjects on computer hardware and software introduction material.